Towards an emerging understanding of non-locality phenomena and non-local transport. (5th January 2015) - Ida, K.; Shi, Z.; Sun, H.J.; Inagaki, S.; Kamiya, K.; Rice, J.E.; Tamura, N.; Diamond, P.H.; Dif-Pradalier, G.; Zou, X.L.; Itoh, K.; Sugita, S.; et al.
Abstract: In this paper, recent progress on experimental analysis and theoretical models for non-local transport (non-Fickian fluxes in real space) is reviewed. The non-locality in the heat and momentum transport observed in the plasma, the departures from linear flux-gradient proportionality, and externally triggered non-local transport phenomena are described in both L-mode and improved-mode plasmas. Ongoing evaluation of 'fast front' and 'intrinsically non-local' models, and their success in comparisons with experimental data, are discussed